«Даўыткөл» суў сақлағышы Сазан – Cyprinus carpio (Linnaeus,1758) балығының паразитофаунасы - Алламуратова, Г.Б.; Хожабаева, Ш.К. (FAN va JAMIYAT, 2021)
The article prorides recommendations on the dynamics of parasitic intestation of carp – cyprinus carpio (Linnaus, 1758) in different ecological conditions of the reservoir “Dautkul” and its prevention.